La réassurance internationale - Gervais, Daniel J. (Assurances)

(untitled) (HEC Montréal, 1988)
The following article by Mr. Daniel J. Gervais provides a clear and concise study of international reinsurance law: its goals, methods and regulations. As the author examines reinsurance law at the international level, Canadian control measures are not discussed. We have therefore asked our collaborator to address this question in a subsequent study, as well as other aspects of reinsurance, particularly facultative cessions which play an important role in international reinsurance contracts and practices as a source of reinsurance law and the rule of arbitration between insurers and reinsurers. In this original and well-documented work, the author discusses the forms of reinsurance and the legal framework in which reinsurance operates. He also examines various international and regional regulations.